Efficient and green microwave-assisted one-pot synthesis of azaindolizines in PEG-400 and water. Issue 21 (1st November 2016) - Wagare, Devendra S.; Farooqui, Mazhar; Keche, Tushar D.; Durrani, Ayesha
ABSTRACT: A facile, convenient, environmentally benign, and one-pot synthesis of imidazo[1, 2-a]pyridines from 2-aminopyridines and in-situ generated phenacyl bromides under microwave irradiation in polyethylene glycol (PEG-400) and water (1:2) has been developed. The protocol provides a better alternative to the existing method as it involves utilization of in-situ-generatedα -bromoacetophenones, avoids the use of lachrymatricα -haloketones as well as volatile toxic organic solvents, and reduces the reaction time to obtain excellent yield. GRAPHICAL ABSTRACT: